Influence of processing parameters on final characteristics of Ni-P-MWCNT coatings produced by pulsed electrodeposition. (3rd September 2022) - Sajedi, B.; Rasooli, A.
ABSTRACT: The aim of the present work is to study the effects of multi-walled carbon nanotubes (MWCNT) concentration and current density on the surface morphology, microhardness, and corrosion resistance of pulsed electrodeposited Ni-P-MWCNT composite coatings. Ni-P-MWCNT composite coatings were deposited on low-carbon steel substrates using different MWCNT concentrations, namely 0.5, 1.0, and 1.5 g L −1 under various current densities of 3, 4, and 5 A dm −2 . The as-produced coatings were characterised using field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), Vickers microhardness measurement, and electrochemical impedance spectroscopy (EIS). To determine the impact of post-heat treatment on the microstructure and microhardness of the coatings, the composite coatings were heat-treated at 400°C for 1 h. Change in the studied variables profoundly altered the final characteristics of the Ni-P deposits. While the incorporation of 1.0 g L −1 MWCNT enhanced the microhardness of the alloy deposit by 560 HV, the microhardness of the composite coating was further increased by 405 HV when it underwent post deposition-heat treatment. The corrosion resistance of the composite coating is about 4 times higher than that of alloy deposits. The optimum mechano-corrosion results were obtained for Ni-P-1.0 g L −1 MWCNT coating fabricated under current density of 4 A dm −2 .